MR Imaging of Relapsing Multiple Sclerosis Patients Using Ultra-Small-Particle Iron Oxide and Compared with Gadolinium - Dousset, V.; Brochet, B.; Deloire, M.S.A.; Lagoarde, L.; Barroso, B.; Caille, J.-M.; Petry, K.G. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Inflammatory multiple sclerosis (MS) lesions are characterized by microglia activation and infiltration of T cells, B cells, and macrophages across the blood-brain barrier (BBB). In the experimental autoimmune encephalomyelitis (EAE) rat model of MS, previous MR imaging investigations with a new contrast agent ultra-small-particle iron oxide (USPIO) that accumulates in phagocytic cells revealed in vivo the presence of macrophage brain infiltration. The goal of this study was to characterize MS lesions with the use of this contrast agent.METHODS: A prospective MR imaging study of 10 patients with MS in acute relapses was achieved by using USPIO and gadolinium.RESULTS: Twenty-four hours after USPIO injection, 33 acute MS lesions in 9 patients showed USPIO uptake. Lesions were seen as high signal intensities on T1-weighted images and low signal intensities on T2-weighted images. Gadolinium enhancement was seen in 31 of these lesions in 7 patients. These 7 patients presented 24 gadolinium-enhanced lesions that did not enhance with USPIO. Two patients showed USPIO-enhanced lesions but no gadolinium-enhanced lesions.CONCLUSION: Taken together with earlier findings obtained in experimental models or in human stroke, the visualization of macrophage activity in vivo with USPIO characterize a distinct cellular and inflammatory event of the dynamic process of MS lesion formation. The macrophage activity information obtained with USPIO is distinct and complementary to the increased BBB permeability seen with gadolinium.